Profil Usahatani Terpadu Sayuran –Ternak Sapi Potong Di Kabupaten Bintan, Kepulauan Riau - Salfina Nurdin Ahmad (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
Integrated Farming profile –Ternak Vegetable Beef Cattle in Bintan regency, Riau Islands The research was conducted in February 2014 - December 2014, this research dilaksananakan in Malang Village Meeting (District of Mount Deer), anculai Ekang Village and Village North Toapaya (Subdistrict Toapaya), Bintan regency. Intake of secondary data and primary data in the form of direct interviews sebanak 25 people then the data generated descriptive ditabulase later. The results showed age of childbearing age with a breeder is still under the age of 50 years, whereas the average farmer's main job is nearly 52%, using waste vegetable culled cows about 24% and 8% use kosentrat rice and composted sewage treatment by means fermentase only 16%, in the event almost all look dull hair and knowledge about worming approximately 52% and approximately 42% bloating disease .. the use of dung as fertilizer generally almost 80% is used to own the remaining approximately 20% sold. State of almost 100% cow disease Anaplasma. Sp.dan after the cows examined terrhadap terlur worm turns cows infected with worms with worm eggs 679-4.600 epg